Analisis Kelayakan Usaha Penggilingan Padi “Berkah Tani” Di Desa Kaliyoso Kecamatan Kangkung Kabupaten Kendal - Putri Amalia Tasbita; Dewi Hastuti; Sri Wahyuningsih; Endah Subekti (CV. ITTC INDONESIA, 2026)
Rice milling is a meeting place for the entire production process such as harvesting, processing and marketing activities of products such as rice and bran. This study aims to analyze the costs, revenues, Break Even Point (BEP) income, and Revenue Cost (R/C) of the “Berkah Tani” rice mill in Kaliyoso Village, Kangkung District, Kendal Regency. The study uses a case study method with quantitative and qualitative approaches. The research location was determined by Purposive Sampling, while respondents were selected using Purposive Sampling. The data used include primary and secondary data analyzed using cost, revenue, income, BEP and R/C analysis. The results of the study show that the total costs incurred in one month are Rp. 23,955,625, total revenue Rp. 33,037,500, income Rp. 10,587,500. BEP service price Rp455/kg, BEP service unit 20,494 kg, BEP price and BEP unit milling service are below the break-even point, BEP price of rice production Rp10,505/kg, BEP unit rice production 1,126 kg, BEP price and BEP unit for rice production business are above the break-even point. The R/C value of milling service activity is 0.88 which means it is not feasible, R/C of rice production activity is 1.64 which means it is feasible to run and the average R/C of “Berkah Tani” rice milling business is 1.38. The R/C value of “Berkah Tani” rice milling business is 1.38 indicating that “Berkah Tani” rice milling business is feasible to run because the R/C value is > 1.